Making sense of strategy - Manning, Anthony D. (AMACOM, 2002)
Business strategy is not rocket science. It's about using pertinent information to make smart decisions, and doing it fast enough to keep your business ahead of the curve. And while many companies have embraced the 24/7 business paradigm, their strategies come from the 9-to-5 era. Plain and simple, most strategic planning efforts fail because they can't keep up with the evolving demands of the market. Standing apart from the piles of discarded management wisdom, Making Sense of Strategy provides real, practical insights and advice for 21st-century businesses. Top strategy consultant Tony Mannin.